Attentional Bias Modification in Virtual Reality – A VR-Based Dot-Probe Task With 2D and 3D Stimuli - Ma, Lichen; Kruijt, Anne-Wil; Nöjd, Sofia; Zetterlund, Elin; Andersson, Gerhard; Carlbring, Per (Frontiers in Psychology, 2019)
Background: Attentional bias modification (ABM) aims to reduce anxiety by attenuating bias towards threatening information. The current study incorporated virtual reality (VR) technology and 3-dimensional stimuli with a dot-probe task to evaluate the effects of a VR-based ABM training on attentional bias and anxiety symptoms. Methods: A total of 100 participants were randomised to four training groups. Attentional bias was assessed at pre- and post-training, and anxiety symptoms were assessed at pre-training, post-training, 1-week follow-up, and 3-months follow-up. Results: Change in anxiety did not correlate with change in bias (p = .24). A repeated-measures ANOVA showed no significant difference in bias from pre- to post-ABM (p = .144), or between groups (p = .976). For anxiety symptoms, a linear mixed-effects model analysis revealed a significant effect of time. Participants showed reduction in anxiety score at each successive assessment (p < .001). However, no other significant main effect or interactions were found. A clinically significant change analysis revealed that 9% of participants were classified as ‘recovered’ at 3-months follow-up. Conclusions: A single session of VR-based ABM did not change attentional bias. The significant reduction in anxiety was not specific to active training, and the majority of participants remained clinically unchanged.